Analisis Anggaran Biaya Dan Pendapatan Produksi Dalam Menunjang Efisiensi Pengendalian Biaya Produksi Pembuatan Keripik Pisang Pada Home Industri Enggar - Wijaya, Agung Dwi Marta; Ni’am, Zaki Bahrun (Jurnal Ilmiah Wahana Pendidikan, 2024)
Controlling production costs is something that companies must do so that production can run smoothly and efficiently. However, it is known that there are still some entrepreneurs who do not understand the preparation of production cost and income budgets, even though with these activities business owners can easily find out the efficiency of activities and costs during production. This research aims to determine the production cost budget and determine the efficiency of controlling production costs in the banana chips manufacturing business in Widoro, Gandusari, Trenggalek. The research method used is descriptive qualitative with data analysis, data collection using interview techniques, observation and documentation. The data used are primary and secondary data. The results of the research can be concluded that the efficiency of controlling production costs in the Enggar banana chips home industry in 2020 has not been achieved, because in 2020 the costs incurred were still too large or exceeded the predetermined budget, namely 10,101,030. for 2021 production cost control was achieved very efficiently, because production cost expenditure was lower than the set budget, namely 7,446,193, while in 2022 production cost control was achieved very efficiently because production cost expenditure was lower of the stipulated budget, namely 332,900.